Soil microbial biomass phosphorus and activity of acid phosphatases during decline of soil available phosphorus - Gatiboni, Luciano Colpo; Kaminski, João; Rheinheimer, Danilo dos Santos; Brunetto, Gustavo (Pesquisa Agropecuaria Brasileira, 2008)
The objective of this work was to evaluate the content of phosphorus stored in the soil microbial biomass and the activity of acid fosfatases, during the decline of soil available phosphorus, caused by successive crops in pot experiment. Samples of Oxisol were utilized with previous addition of soluble phosphates (0, 180, 360, 540, and 720 kg ha-1 of P2O5), applied in six consecutive years. The soil samples were submitted to 15 successive crops in greenhouse, without replacement of absorbed phosphorus by plants. After each three successive crops, soil was sampled, and the following variables were determined: the available phosphorus by anion exchange resin, phosphorus stored in the soil microbial biomass and the activity of acid phosphatases. As a consequenceof the reduction of the soil available phosphorus, the amount of microbial phosphorus decreased, and the activity of phosphatases increased. In soils with low phophorus content and no plant residues, the microbial P has little importance for plant nutrition.